Obesity among females in Al-Sader city Baghdad, Iraq, 2017. - Jasim, Hadeel M.; Abdul Hussein, Hassan M.; Al-Kaseer, Eman A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: obesity is a serious public health problem. Literatures in Iraq explained that obesity due tochange in economy and Lifestyles.Objective: To report on prevalence of obesity among women in Al- sader City, Baghdad. 2017.Method: A total of 440 females were included in this study. They were Selected randomly from relativesto patients accompanied them In attending to primary health care centers. BMI (body mass index) toassess the Weight. Demo-graphic data were requested too.Result: The prevalence of obesity was 35.2%. Age , education, divorced Widows were determinants ofobesity. Employment and crowding Index (socioeconomic status) were not obvious determinants ofobesity.Conclusion: High prevalence of obesity was observed.